The Current and Desirable States of the Education Management Reform for Quality Citizenship in the Kingdom of Cambodia - Hang-Chuon, Naron; Siribanpitak, Pruet; Usaho, Chayaphim (Scholar: Human Sciences, 2019)
The objectives of this study were 1) To study the conceptual framework of education management reform and quality citizenship; 2) To study the current and desirable states of education management reform for enhancing the quality citizenship in Cambodia. The samples were 710 respondents, consisting of education policymakers, department Directors, school administrators, teachers, School Support Committee, students and stakeholders. The data were analyzed using descriptive statistics to find out the mean and S.D. The findings of the study revealed that 1) conceptual framework of education management reform consists of four components: administrative management, academic management, education finance managent, and personnel management reform, and the conceptual framework of the quality citizenship consists of quality national citizen and global citizen, and 2) the overall current states of the education management reform is at a middle level (M=3.13; S.D =0.66) in all aspects, and desirable states of the education management reform is at the high level (M=4.28; S.D=0.53).